MODEL STRATEGI PROMOSI PARIWISATA BERBASIS EKOWISATA DENGAN PENDEKATAN SYARIAH DI KABUPATEN BANYUWANGI - Samsuri Samsuri; Ficky Septalinda (Islamic Banking Department, Faculty of Islamic Economics and Business, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, Indonesia., 2022)
This study aims to examine whether the promotional strategy carried out in order to introduce ecotourism-based Banyuwangi tourism is in accordance with the sharia approach, considering that Banyuwangi has quite a number of ecotourism-based tourism objects that are feasible to be developed, so that it is expected to be able to increase community and regional income. So this study aims to determine the strategy of tourism promotion based on ecotourism with a sharia approach. The research is a field research with a qualitative approach, collecting data using the methods of observation, interviews, and documentation. While the analysis uses qualitative data analysis (non-statistical). Based on the results of the study, it shows that the ecotourism promotion strategy carried out by Disbudpar is in accordance with the sharia approach, namely honesty, sincerity and trust, and judging from the ethics of promotion in Islam, it also does not sell oaths, does not break promises, is honest, avoids fraud, and is willing to make small profits. but a blessing and the most important thing is to prioritize the welfare of the community.